Advances, applications, and limitations of portable and rapid detection technologies for routinely encountered foodborne pathogens - Quintela, Irwin A.; Vasse, Tyler; Lin, Chih-Sheng; Wu, Vivian C. H. (Frontiers in Microbiology, 2022)
Traditional foodborne pathogen detection methods are highly dependent on pre-treatment of samples and selective microbiological plating to reliably screen target microorganisms. Inherent limitations of conventional methods include longer turnaround time and high costs, use of bulky equipment, and the need for trained staff in centralized laboratory settings. Researchers have developed stable, reliable, sensitive, and selective, rapid foodborne pathogens detection assays to work around these limitations. Recent advances in rapid diagnostic technologies have shifted to on-site testing, which offers flexibility and ease-of-use, a significant improvement from traditional methods' rigid and cumbersome steps. This comprehensive review aims to thoroughly discuss the recent advances, applications, and limitations of portable and rapid biosensors for routinely encountered foodborne pathogens. It discusses the major differences between biosensing systems based on the molecular interactions of target analytes and biorecognition agents. Though detection limits and costs still need further improvement, reviewed technologies have high potential to assist the food industry in the on-site monitoring and screening of foodborne pathogens and other hazards to maintain safe and healthy foods. Finally, this review offers targeted recommendations for future development of diagnostic tools specifically for emerging and re-emerging foodborne pathogens.